2006
DOI: 10.1074/jbc.m510278200
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus CDC7/DRF1 Complex Is Required for the Initiation of DNA Replication

Abstract: The Cdc7 kinase is essential for the initiation of DNA replication in eukaryotes. Two regulatory subunits of the Xenopus Cdc7 kinase have been identified: XDbf4 and XDrf1. In this study we determined the expression pattern of XDbf4 and XDrf1 and examined their involvement in DNA replication. We show that XDrf1 expression is restricted to oogenesis and early embryos, whereas XDbf4 is expressed throughout development. Immunodepletion from Xenopus egg extracts indicated that both proteins are only found in comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…DDK interacts stably with pre-RCs (Takahashi and Walter 2005;Silva et al 2006) and with Scc2-Scc4 (this study), suggesting that DDK plays a structural role in Scc2-Scc4 recruitment. Importantly, we also showed that the protein kinase activity of DDK is required to promote Scc2-Scc4 loading onto chromatin.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…DDK interacts stably with pre-RCs (Takahashi and Walter 2005;Silva et al 2006) and with Scc2-Scc4 (this study), suggesting that DDK plays a structural role in Scc2-Scc4 recruitment. Importantly, we also showed that the protein kinase activity of DDK is required to promote Scc2-Scc4 loading onto chromatin.…”
Section: Discussionsupporting
confidence: 58%
“…Cdc7-Dbf4 and Cdc7-Drf1 are often referred to as DDK (Dbf4-or Drf1-dependent kinase). During Xenopus early embryogenesis, Drf1 is the predominant activator of Cdc7, while in somatic cells, Dbf4 likely plays a more prominent role (Takahashi and Walter 2005;Silva et al 2006).…”
mentioning
confidence: 99%
“…Although the Cdc7 protein level is constant during the cell cycle, its kinase activity fluctuates during this period because of its binding to the regulatory subunit, Dbf4, whose level peaks at S phase (3,4). Whereas only one regulatory subunit has been identified in yeast systems, mammals and Xenopus contain an additional regulatory subunit, Drf1 (5). Both Dbf4 and Drf1 appear to be important for DNA replication (3,5).…”
mentioning
confidence: 99%
“…Whereas only one regulatory subunit has been identified in yeast systems, mammals and Xenopus contain an additional regulatory subunit, Drf1 (5). Both Dbf4 and Drf1 appear to be important for DNA replication (3,5).…”
mentioning
confidence: 99%
“…Hence, the relationship between Cdc7 and Dbf4/Drf1 is functionally analogous to the cyclin-dependent kinase/cyclin relationship (5,6). In early Xenopus embryos, Drf1 is the primary Cdc7-binding partner that drives replication (7,8). The most well established target of DDK activity is the MCM2-7 complex, which is an important constituent of the putative replicative helicase.…”
mentioning
confidence: 99%